Breast-conserving surgery versus mastectomy for treatment of breast cancer after neoadjuvant chemotherapy - Song, Yu-Chun; Huang, Zhou; Fang, Hui; Tang, Yu; Jing, Hao; Song, Yong-Wen; Jin, Jing; Liu, Yue-Ping; Chen, Bo; Tang, Yuan; Qi, Shu-Nan; Lu, Ning-Ning; et al. (Frontiers in Oncology, 2023)
Background: To compare recurrence and survival outcomes between breast-conserving surgery (BCS) and mastectomy after neoadjuvant chemotherapy (NACT).The data of 730 patients who underwent NACT between 2000 and 2014 were retrospectively reviewed: . A total of 104 (14.2%) patients received BCS and 626 (85.8%) received mastectomy. Locoregional recurrence (LRR), distant metastases (DM), disease-free survival (DFS), breast cancer-specific survival (BCSS), and overall survival (OS) were analyzed using the Kaplan-Meier method. The impact of BCS versus mastectomy on outcomes was assessed by multivariate Cox models. Inverse probability of treatment weighting (IPTW) was used to balance covariates between the two groups.The median follow-up of BCS and mastectomy groups were 86.5 and 87.4 months, respectively. There were significant differences in distribution of most baseline characteristics This is a provisional file, not the final typeset article between two groups. The 5-year LRR, DM, DFS, BCSS, and OS after BCS and mastectomy were 6.9% vs. 7.6% (P = 0.805), 10.8% vs. 19.9% (P = 0.145), 83.4% vs. 78.2% (P = 0.514), 98.9% vs. 90.4% (P = 0.005), and 98.9% vs. 90.1% (P = 0.003), respectively. Compared with those who underwent mastectomy, the patients with BCS had similar 5-year LRR, DM, and DFS rates, but had significantly higher 5-year BCSS (98.9% vs. 90.4%, P = 0.005) and OS (98.9% vs. 90.1%, P = 0.003) rates. Multivariate analysis also showed that BCS had no significant impact on LRR, DM, and DFS compared with mastectomy; but BCS significantly improved BCSS (HR = 0.27, 95% CI: 0.08-0.85, P = 0.025) and OS (HR = 0.25, 95% CI: 0.08-0.79, P = 0.018). After IPTW adjustment, the LRR, DM, DFS, BCSS and OS between two groups had no significant differences.The recurrence and survival outcomes are comparable with BCS and mastectomy. Thus, BCS is a safe treatment option for selected breast cancer patients after NACT.